Quality of life of tinnitus patients with and without hearing loss - Ayodele, Oluyomi S.; Segun-Busari, Segun Segun-Busari; Omokanye, Kayodele H.; Dunmade, David A.; Ologe, Emmanuel F. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Tinnitus is a common, irritating and often disturbing symptom. It poses big challenge to the patients’ management and affects their quality of life (QoL). Tinnitus is one of the most common otological symptoms associated with hearing loss. The aim of the study was to determine the quality of life of adult tinnitus patients and the effect presence of hearing loss has on the quality of life. Methods: All consenting adults presenting with tinnitus with or without associated hearing loss were recruited. Sociodemographic information, clinical assessment, pure tone audiometry (PTA) and QoL assessment with Tinnitus Functional Index (TFI) were carried out. The data collected were analysed and results were presented in tables and simple chart. Results: The age range of participants was between 18 and 80 years with a mean age of 51.94 years±17.41. Male to female ratio was 1:1.4. The relationship between tinnitus and associated hearing loss was statistically significant with moderate hearing loss found as commonest. Sensorineural hearing loss was the commonest type found. Tinnitus was mostly described as a big problem. The relationship between the TFI scores and presence of hearing loss as well as degree of hearing loss was statistically significant. Conclusions: Tinnitus has a significant health burden which tends to increase with co-existing hearing loss. PTA assessment and measurement of QoL should be advocated as routine for tinnitus patients no matter the cause of tinnitus and also especially among those with self-professed normal hearing.